Electron-impact ionization of W25+. (23rd August 2016) - Kynienė, A; Pakalka, S; Masys, Š; Jonauskas, V
Abstract: Electron-impact ionization cross sections for the ground level of the W 25+ ion have been investigated by performing level-to-level calculations and using the Dirac–Fock–Slater method in the single-configuration approach. The main attention has been focused on the influence of the increasing principal and orbital quantum numbers on the excitation-autoionization (EA) process and its contribution to the total ionization cross sections. The obtained results demonstrate that excitations to the high- nl shells ( n ≥ 9 ) increase cross sections of the indirect ionization process by about 60% compared to the excitations to the lower shells ( n ≤ 8 ). It was established that excitations to the shells with the orbital quantum number l = 4 give the greatest contribution to EA. Maxwellian rate coefficients derived from the cross sections for the ground state are compared with the previously obtained values from the configuration-average distorted-wave (CADW) approximation. The rate coefficients for direct ionization (DI) are smaller than the corresponding CADW values, while the EA rate coefficients are larger than the ones from the CADW calculations. The total DI+EA rate coefficients are about 20% larger than the CADW rate coefficients.